Do computer generated ECG reports improve interpretation by accident and emergency senior house officers?. Issue 909 (1st July 2001) - Goodacre, S; Webster, A; Morris, F
Abstract : OBJECTIVES: To determine whether access to a computer generated electrocardiogram (ECG) report can reduce errors of interpretation by senior house officers (SHOs) in an accident and emergency department. METHODS: Ten SHOs were asked to interpret 50 ECGs each: 25 with computer generated reports, 25 without. Their answers, and the computer generated reports, were compared with a "gold standard" produced by two experienced clinicians. The primary outcome measure was the proportion of major errors of interpretation. RESULTS: The computer reading system made two major errors (4%, 95% confidence interval (CI) 1.1% to 13.5%) compared with the gold standard. Access to the computer report did not significantly reduce major errors among SHOs (46 (18.4%) with report v 56 (22.4%) without, odds ratio 0.64, 95% CI 0.36% to 1.14%, p=0.13) or improve the proportion completely correct (104 (41.6%) with report v 91 (36.4%) without, odds ratio 1.43, 95% CI 0.88 to 2.33, p=0.15). CONCLUSIONS: SHOs have a high error rate when interpreting ECGs, which is not significantly reduced by access to a computer generated report. Junior doctors should continue to seek expert senior help when they have to interpret a difficult ECG.